Construct Validation of a New Instrument to Measure Declarative Tactical Knowledge in Basketball. Issue 4 (August 2021) - Reis, Cleiton Pereira; Morales, Juan Carlos Pérez; Gomes, Cristiano Mauro Assis; Pereira, Fernando de Azevedo Alves; Ibáñez, Sergio José
Measuring basketball players' declarative tactical knowledge is relevant to the teaching and learning process. In this study we aimed to verify the construct validity and construct reliability of the Instrument for Measuring Declarative Tactical Knowledge in Basketball (IMDTK-Bb). We recruited 1, 188 male basketball athletes aged 10-19 years old. We used confirmatory factor analysis with weighted least squares mean and variance estimator for construct validation and MacDonald´s omega for internal consistency. We established a final model with 17 scenes referring to the declarative tactical knowledge and type of action players used to solve game situations the scenes represented. The final model presented a good Comparative Fit Index (CFI = 1.000), Tucker–Lewis Index (TLI = 1.001) and Root Mean Square Error of Approximation (RMSEA = .000). The reliability index was .779. We conclude that the IMDTK-Bb has good construct validity and can be used in further research.